Horizontal Fracture Formation in the Cenozoic Mudstone of the Western Qaidam Basin - Li, Jian; Li, Qi; Zeng, Lianbo; Zhu, Zhenjun; Ding, Xiaojun; Li, Xianming (Frontiers in Earth Science, 2022)
Fractures can provide valuable information on the tectonic evolution of the Earth’s crust. Our field observation data, rock core data, and thin section observations reveal several horizontal fractures in the Cenozoic mudstone strata in the western Qaidam Basin, Qinghai Province, China. These horizontal fractures have rough surfaces and are filled by gypsum. The fractures are mainly curved; however, some straight fractures are also found. There are many intersections between adjacent curved fractures, which often adjoin to form ‘T’ shape fractures. Fracture apertures are mainly between 1 mm and 1 cm, with a maximum of 3 cm. Both the size and density of fractures decrease as strata denudation thickness decreases and depth of burial increases. Horizontal fractures are only found in a core area of anticlines with severe strata denudation. Accordingly, these fractures are related to vertical extension due to residual stress in the process of rapid uplift and denudation. The horizontal fractures cut earlier vertical tectonic fractures, indicating their formation after tectonic extrusion. Electron spin resonance (ESR) dating of fracture-filling materials revealed that horizontal fractures appeared in two stages. The first stage was approximately 1.8 Ma ago, while the second stage was approximately 0.3 Ma ago. The size and density of the later-stage horizontal fractures are markedly greater than the earlier-stage fractures. Based on the driving stress when fractures are formed, which is obtained from fracture parameters, the denudation rate in the later stage was approximately 2~3-fold greater than that in the earlier stage. According to the evidence, during the Quaternary, the western Qaidam Basin experienced pulsating tectonic extrusion, producing uplift and denudation and an increase in tectonic activity. Such findings suggest a gradual increase in episodic tectonic activity in the entire Tibetan Plateau region during the Quaternary.